Levantamento das principais plantas tóxicas de interesse pecuário para bovinos no município de Rio Verde-GO - Francischini, Cristiane Raquel Dias [UNESP] (2014)
In Brazil ingestion of toxic plants cause substantial economic losses in extensive cattle ranching. It is known that the study of plants in areas with little research enables the inclusion of plants that occur in a given region to cause poisoning of the cattle. This increases the need to monitor the plant species in a given geographic region. The objective was to determine the toxic plants of interest that occur livestock in pastures and edges of savanna in Rio Verde -GO. Analyzed a total of 13,630 hectares, equivalent to 8 % of pastures in the county in focus. These areas were inspected them and plant material collected for later identification. Of these , based on the frequency of the dry season , the main plants found were Crotalaria spectabilis , Senna obtusifolia , Lantana camara , Pteridium aquilinum , mollis Dimorphandra , Enterolobium contortisiliquum and , in the rainy season , those with the greatest frequency were Crotalaria spectabilis , Lantana camara , Pteridium aquilinum , Senna obtusifolia . The householders were unable to associate the presence of toxic plants in pastures with possible signs of disease in the herd. Concludes that the study needs of educational campaigns and extension so that there is awareness of the toxicity of weeds found so that they can be eradicated from the pastures or precautions taken mainly in the dry season where there is scarcity of pasture and municipality where some of these plants that are typical savanna trees, provide a desirable addition to shadow, its fruits (pods) toxic